2020
DOI: 10.1080/07391102.2020.1798285
|View full text |Cite
|
Sign up to set email alerts
|

Identification of some novel oxazine substituted 9-anilinoacridines as SARS-CoV-2 inhibitors for COVID-19 by molecular docking, free energy calculation and molecular dynamics studies

Abstract: Coronavirus disease (COVID-19), a life-threatening disease, is caused by SARS-CoV-2. The targeted therapeutics of small molecules helps the scientific community to fight against SARS-CoV-2. In this article, some oxazine substituted 9-anilinoacridines (A1-A48) was designed by docking, MM-GBSA and molecular dynamics (MD) simulation studies for their COVID-19 inhibitory activity. The docking of ligands A1-A48 against SARS-CoV-2 (PDB ID: 5R82) are performed by using Glide module, in silico ADMET screening by QikPr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…However, in the original publication from which the source data for case study 1 was obtained, pladienolide B, 2-deoxy-d-Glucose, ribavirin and NMS-873 were identified as potential drugs of interest [ 3 ], which target various components of the RNA processing and protein machinery, along with glycolysis. In contrast, our list of highest scoring candidates is the anti-cancer drugs amsacrine, ceritinib and crizotinib targeting cell cycle and cell growth pathways, which is supported by some experimental [ 20 ] and theoretical evidence [ 5 , 34 ]. In the first scenario, inhibiting cell metabolism, RNA splicing and translation would limit many biological processes in the cell, including that of some viruses [ 15 ].…”
Section: Discussionmentioning
confidence: 82%
“…However, in the original publication from which the source data for case study 1 was obtained, pladienolide B, 2-deoxy-d-Glucose, ribavirin and NMS-873 were identified as potential drugs of interest [ 3 ], which target various components of the RNA processing and protein machinery, along with glycolysis. In contrast, our list of highest scoring candidates is the anti-cancer drugs amsacrine, ceritinib and crizotinib targeting cell cycle and cell growth pathways, which is supported by some experimental [ 20 ] and theoretical evidence [ 5 , 34 ]. In the first scenario, inhibiting cell metabolism, RNA splicing and translation would limit many biological processes in the cell, including that of some viruses [ 15 ].…”
Section: Discussionmentioning
confidence: 82%
“…As a result, the free binding energy (Δ G bind ) of the examined systems can be calculated. The binding energy (Δ G bind ) of the complexes can be calculated according to eq , normalΔ G bind = E complexe ( minimized ) + E ligand ( minimized ) E receptor ( minimized ) …”
Section: Methodsmentioning
confidence: 99%
“…The time course of MD simulation was fixed in 100 ns using the Desmond package of Schrödinger 2020-3 software . The examined systems were solvated using the orthorhombic single point charge (SPC) explicit water model. , To improve and regenerate the protein–ligand systems, the optimized potentials for liquid simulations extended (OPLSe) force field was used. , By adding sodium and chloride ions to the total complexes explored, the charge was neutralized. In addition, the energies of the systems were minimized by 2000 steps before running the MD simulation along a 100 ns path in the NPT ensemble .…”
Section: Methodsmentioning
confidence: 99%
“…Fakhar et al screened 3435 anthocyanin substructure compounds by docking and MM/GBSA calculations, reporting the best compound to be 44256921. Some other compounds, such as α-ketoamide covalent inhibitors, macrolactin compounds, echinocandins, essential oil compounds, glucocorticoids, angucycline compounds, hydroxychloroquine derivatives, aminoglycosides, imidazole derivatives, Se-containing heterocyclic compounds, circadian clock modulating compounds, oxazine substituted 9-anilinoacridines, nitric oxide donor furoxan, nitric oxide donor heterocyclic vasodilators, withanone caffeic acid phenethyl ester, tetracycline, β-glutamyl- S -allylcysteine peptides, and others, were also screened by docking and MM/PB­(GB)­SA simulations. …”
Section: Methods and Approachesmentioning
confidence: 99%